Penggunaan Gabapentin dan Pregabalin sebagai Terapi Adjuvant pada Pasien Nyeri di Instalasi Rawat Inap Rumah Sakit Umum Daerah Ungaran: Overview of The Use of Gabapentin and Pregabalin as Adjuvant Therapy in Inpatient Pain Patients Ungaran Hospital - Muhamad Ilham Rusdi; Neli Diah Pratiwi (Indonesian Journal of Pharmacy and Natural Product, 2025)
Unpleasant sensory and emotional experiences due to tissue damage are often felt by everyone. Management of neuropathic, nociceptive and mixed pain often uses pregabalin and gabapentin. The purpose of this study was to describe the use of gabapentin and pregabalin as adjuvant therapy in inpatients with pain at Ungaran Hospital. This study was non-experimental using a descriptive observational method using secondary data obtained from medical records at Ungaran Hospital with a sample of 43 medical record data. The data collected were then subjected to descriptive analysis which included patient characteristics based on gender, age, clinical symptoms, and comorbidities. The description of the use of Atrial Fibrillation drugs included drug classes and types of drugs then calculated the percentage non-experimental with a descriptive research method and data collection was carried out retrospectively with a purposive sampling technique, namely 43 samples. Data were analyzed descriptively. The results of patients who received adjuvant gabapentin and pregabalin therapy were mostly aged 56-65 years (35%) and women (60%). The majority of patients experienced moderate pain (70%) and neuropathic pain (60%). The most common adjuvant therapies were gabapentin (86%), and pregabalin use (14%).   ABSTRAK Kerusakan jaringan dapat menyebabkan pengalaman sensorik dan emosional yang tidak menyenangkan sering sekali dirasakan oleh semua orang. Manajemen penatalaksanaan nyeri neuropatik, nosiseptif dan campuran sering kali digunakan pregabalin dan gabapentin. Tujuan penelitian ini analisis gambaran penggunaan gabapentin dan pregabalin sebagai terapi adjuvant pada pasien nyeri di rawat inap. Penelitian ini bersifat non eksperimental menggunakan metode deskriptif observasional dengan menggunakan data sekunder yang diperoleh dari rekam medis Rumah Sakit Daerah Ungaran dengan jumlah sampel 43 data rekam medik. Data yang terkumpul  kemudian dilakukan analisis deskriptif yang meliputi: karakteristik pasien berdasarkan jenis kelamin, usia, gejala klinis, dan penyakit penyerta. Gambaran penggunaan obat Atrial Fibrilasi meliputi golongan obat dan jenis obat kemudian menghitung persentasenyanon-ekperimental dengan metode penelitian deskriptif dan pengambilan data dilakukan secara retrospektif dengan teknik pengambilan menggunakan purposive sampling yaitu 43 sampel. Data dianalisis secara deskriptif.       Hasil pasien yang mendapatkan terapi adjuvant gabapentin dan pregabalin sebagian besar berusia  56-65 tahun (35%) dan perempuan (60%). Mayoritas pasien mengalami nyeri sedang (70%) dan nyeri neuropatik (60%). Terapi adjuvan yang paling umum adalah gabapentin (86%), dan penggunaan pregabalin  (14%).